Pengaruh Perputaran Modal Kerja, Pertumbuhan Penjualan, dan Perputaran Persediaan terhadap Kinerja Keuangan dengan Struktur Modal sebagai Variabel Moderasi - Josephin Kezia; Erny Luxy D. Purba (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the impact of working capital turnover, sales growth, and inventory turnover on financial performance, with capital structure as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The panel data includes 153 companies, resulting in 459 observations, which were then filtered outliers to 359 observations. The analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with a pooled Ordinary Least Squares (OLS) approach. The findings reveal that working capital turnover and inventory turnover have a positive and significant effect on financial performance (p < 0.05), while sales growth is insignificant (p > 0.05). Furthermore, capital structure is not shown to moderate this relationship. These results imply that financial performance is more influenced by operational efficiency than by financing.